Cannabis Use in Patients With Cancer: A Clinical Review. Issue 11 (24th November 2022) - Worster, Brooke; Hajjar, Emily R.; Handley, Nathan
Abstract : Cannabis use and interest continues to increase among patients with cancer and caregivers. High-quality research remains scant in many areas, causing hesitancy or discomfort among most clinical providers. Although we have limitations on hard outcomes, we can provide some guidance and more proactively engage in conversations with patients and family about cannabis. Several studies support the efficacy of cannabis for various cancer and treatment-related symptoms, such as chemotherapy-induced nausea and cancer pain. Although formulations and dosing guidelines for clinicians do not formally exist at present, attention to tetrahydrocannabinol concentration and understanding of risks with inhalation can reduce risk. Conflicting information exists on the interaction between cannabis and immunotherapy as well as estrogen receptor interactions. Motivational interviewing can help engage in more productive, less stigmatized conversations.